Malaysia: Balancing National Development, National Security and Cybersecurity Policy - El-Muhammady, Ahmad (Routledge, 2021)
The purpose of this chapter is threefold. First, to examine the Internet booms and the growth of the Information and Communication Technology (ICT) in Malaysia and how it impacts Malaysia’s national security. Second, it also examines the nature and substance of Malaysia’s cybersecurity frameworks. Third, it discusses Malaysia’s strategy to manage the multitude of cybersecurity challenges within its border, including the emerging trend of security threats such as cyber warfare, cyberterrorism, and cybercrime.